2014
DOI: 10.4236/jss.2014.29046
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Science Activities in an Inclusive Elementary Classroom

Abstract: As elementary teachers engage their students in scientific inquiry, they often turn to the internet as a resource for rapidly locating scientific activities to use in an inclusive classroom. In these circumstances, however, how can the elementary level teacher know whether the science activities are safe? Even if safety is included within the activities, how does the elementary level teacher know if all safety issues have adequately been addressed? The purpose of this article is to highlight potential safety c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In conclusion, if an activity is determined to be unsafe to use in the classroom, the high school physics teacher can modify the activity to make it safe. If the activity cannot be modified to ensure safety, then a different, safe activity should be substituted [2] [3].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In conclusion, if an activity is determined to be unsafe to use in the classroom, the high school physics teacher can modify the activity to make it safe. If the activity cannot be modified to ensure safety, then a different, safe activity should be substituted [2] [3].…”
Section: Resultsmentioning
confidence: 99%
“…Students are to follow the general laboratory safety guidelines as provided by the physics teacher. Because moving parts can present a hazard, students are to avoid wearing baggy clothing, avoid wearing big, bulky jewelry, tie back long hair, avoid bringing unnecessary materials to the laboratory, e.g., cell phones, book bags, purses, and remove all ear phones/ear buds in the laboratory area [2]. Students are to wear closed-toed shoes.…”
Section: General Laboratory Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a study by Bulfin & North (2008) revealed a clear correlation between substance abuse and lower standardized test scores among elementary school students, indicating the detrimental influence of drugs on academic achievement. Similarly, research conducted by (Meier et al, 2014) emonstrated a link between drug use during childhood and increased likelihood of behavioral problems, disciplinary issues, and poor attendance in primary schools.…”
Section: Introductionmentioning
confidence: 99%